Cross-Talk Signaling in Rice During Combined Drought and Bacterial Blight Stress - Vemanna, Ramu S.; Bakade, Rahul; Bharti, Pooja; Kumar, M. K. Prasanna; Sreeman, Sheshshayee M.; Senthil-Kumar, Muthappa; Makarla, Udayakumar (Frontiers in Plant Science, 2019)
Due to climatic changes rice crop is affected by moisture stress and pathogens. Tissue water limitation besides reducing growth rates, also renders the crop susceptible to the infection by Xanthomonas oryzae pv. oryzae (Xoo) that causes bacterial leaf blight. Independently, both drought adaptation and Xoo resistance have been extensively studied. Though the cross-talk between drought and Xoo stress responses have been explored from individual stress studies, examining the combinatorial stress response is limited in rice. Recently published combined stress studies showed that under the combined stress, maintenance of carbon assimilation is hindered and such response is regulated by overlapping cellular mechanisms that are different from either of the individual stresses. Several receptors, MAP kinases, transcription factors and ribosomal proteins, are predicted for playing a role in cellular homeostasis and protects cells from combined stress effects. Here we provide a critical analysis of these aspects using information from the recently published combined stress literature. This review is useful for researchers to comprehend combinatorial stress response of rice plants to drought and Xoo.